Biophysical and nutritional combination treatment for myosteatosis in patients with sarcopenia: a study protocol for single-blinded randomised controlled trial - Maoyi Tian; Ling Qin; Simon Kwoon Ho Chow; Wing Hoi Cheung; A A Welch; Can Cui; Parco M Siu; Meng Chen Michelle Li; Yu Kin Cheng; Ronald Man Yeung Wong; Timothy CY Kwok; Minghui Yang; et al. (BMJ Open)
Introduction Sarcopenia is characterised by age-related loss of skeletal muscle and function and is associated with risks of adverse outcomes. The prevalence of sarcopenia increases due to ageing population and effective interventions is in need. Previous studies showed that β-hydroxy β-methylbutyrate (HMB) supplement and vibration treatment (VT) enhanced muscle quality, while the coapplication of the two interventions had further improved muscle mass and function in sarcopenic mice model. This study aims to investigate the efficacy of this combination treatment in combating sarcopenia in older people. The findings of this study will demonstrate the effect of combination treatment as an alternative for managing sarcopenia.Methods and analysis In this single-blinded randomised controlled trial, subjects will be screened based on the Asian Working Group for Sarcopenia (AWGS) 2019 definition. 200 subjects who are aged 65 or above and identified sarcopenic according to the AWGS algorithm will be recruited. They will be randomised to one of the following four groups: (1) Control+ONS; (2) HMB+ONS; (3) VT+ONS and (4) HMB+VT + ONS, where ONS stands for oral nutritional supplement. ONS will be taken in the form of protein formular once/day; HMB supplements will be 3 g/day; VT (35 Hz, 0.3 g, where g=gravitational acceleration) will be received for 20 mins/day and at least 3 days/week. The primary outcome assessments are muscle strength and function. Subjects will be assessed at baseline, 3-month and 6-month post treatment.Ethics and dissemination This study was approved by Joint CUHK-NTEC (The Chinese University of Hong Kong and New Territories East Cluster) Clinical Research Management Office (Ref: CRE-2022.223-T) and conformed to the Declaration of Helsinki. Trial results will be published in peer-reviewed journals and disseminated at academic conferences.Trial registration number NCT05525039.